Temperature control strategy and simulation analysis of a walking beam reheating furnace - Xiaobo Qu; Ruowei Li; Caiyi Liu; Silvia Barella; Zhihao Ni; Yang Liu; Shuo Guo; Shicheng Liang; Sunrui Tao; Yan Peng; De Li; Andrea Gruttadauria; et al. (Materials Research Express)
As a critical intermediate stage in the continuous casting and rolling process for bar production, the heating quality of a walking beam reheating furnace significantly affects billet shaping and the performance of the finished bars. To address issues such as uneven billet temperature distribution during heating, which leads to non-uniform deformation resistance in the rolling process, causing bending deformation, excessive thermal stress, and the initiation of microcracks and propagation of inherited casting cracks, this study uses 20CrNiMoA steel billets as the research object. The temperature field distribution inside the walking beam reheating furnace was simulated with ABAQUS finite element software. The accuracy of the simulation results was verified through ‘black box’ experiments, which demonstrated that the simulation precision meets the standards required for industrial applications. On this basis, the study systematically investigated the effects of temperature and time parameter settings in different heating zones of the furnace on billet temperature distribution and stress evolution. The results show that increasing the charging temperature improves temperature distribution and peak stress during the preheating stage, while lower furnace temperatures during the preheating phase reduce excessive thermal stress, and optimal furnace settings in heating zone I and II enhance heating efficiency and uniformity. The findings provide theoretical foundations and data support for optimizing on-site production heating process parameters and improving billet heating quality.